Changes in Working Conditions and Mental Health Among Intensive Care Physicians Across a Decade - Beschoner, Petra; von Wietersheim, Jörn; Jarczok, Marc N.; Braun, Maxi; Schönfeldt-Lecuona, Carlos; Jerg-Bretzke, Lucia; Steiner, Laurenz (Frontiers in Psychiatry, 2020)
Background: International studies have shown that among physicians working in intensive care, a relatively high level of work load, an elevated risk of developing burnout and reduced mental health are frequent. The implementation of a legislative intervention in Germany with the goal to reduce the working hours of physicians, offered an opportunity to investigate the potential influence of occupational conditions on stress and mental health. The present study investigates working conditions, occupational stress and burnout risk in two samples of German Intensive Care Physicians in 2006 and 2016. The aim was to assess how occupational and private stress factors influenced burnout and effort-reward imbalance indices over this time-period. Methods: Intensive care physicians were surveyed during the annual conference of their profession in two cross-sectional studies (10-year gap). Data on demographic (occupational, family), medical history and mental health (burnout and effort-reward imbalance) were assessed by paper pencil questionnaires. Results: In total, N = 2085 physicians participated (2006: N = 1403, 2016: N = 695), with N=1840 (2006 = 1248; 2016= 592) eligible for propensity score matching comparison. In general, more working hours per week and working days on weekends were associated with an increased effort/reward imbalance and higher burnout scores. From 2006 to 2016, reductions in working hours per week and days worked on weekends were accompanied by improvements in occupational stress (effort/reward imbalance) and by trend in mental health indices (burnout) after matching for differences in working conditions. Conclusions: The study presents the changes concerning occupational stress factors and mental wellbeing in physicians working in intensive care in 2016 as compared to 2006. These findings may promote the implementation of preventive strategies in the vocational context to protect health and productivity of physicians, especially intensive care physicians.